Bimetallic mesoporous cerium and copper-based nanoplatform with stearoyl CoA desaturase inhibitor and indocyanine green co-delivery for synergistic pancreatic tumor suppression - Ruihe Zheng; Yanan Yang; Peng Zhang; Xiaona Han; Minqin Huang; Yuxia Wu; Yuhang Li (Materials & Design, 2025)
Pancreatic ductal adenocarcinoma (PDAC) is characterized by an unfavorable prognosis, with a combined five-year survival rate below 5 % across all diagnostic stages. Despite surgical advancements marginally improving survival outcomes, clinical efficacy remains suboptimal. Concurrently, chemodynamic therapy (CDT) and photothermal therapy (PTT) have emerged as synergistic modalities for tumor eradication with enhanced safety profiles. In this study, we engineered bimetallic mesoporous CeCu-based nanocarriers through a simplified synthesis route to co-encapsulate, a stearoyl-CoA desaturase 1 (SCD1) inhibitor, A939572 and indocyanine green (ICG). Subsequent RGD peptide surface modification yielded a tumor-targeted nanosystem with pH-responsive drug release capabilities. The acidic tumor microenvironment triggers simultaneous liberation of therapeutic agents and dissolution of Ce/Cu ions for tumor cell effective killing via PTT-enhanced CDT through ion-mediated ROS amplification and SCD1 signaling blockade. Preclinical evaluations demonstrated potent tumor suppression via this multimodal approach while maintaining favorable biocompatibility. This strategy presents a novel paradigm for optimizing therapeutic payload delivery and multimodal tumor eradication in aggressive malignancies.